2009
DOI: 10.1007/s11295-009-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stability of wood density and diameter in Pinus radiata D. Don plantation estate across Australia

Abstract: Genetic variation for wood quality traits and diameter growth for radiata pine (Pinus radiata D. Don) at age 20/21 years was estimated from eight trials in Australia. The traits studied were wood density, acoustic time-offlight (an indirect measure of stiffness) and diameter at breast height (DBH). Wood density and DBH exhibited significant additive genetic variation whereas non-additive effects were not significantly different from zero. Time of flight was also not significantly different from zero for both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
7
25
2
Order By: Relevance
“…Inheritance of ED have been investigated during the last decade mainly concentrated in temperate species (CHERRY et al, 2008;DUNGEY et al, 2006;HANNRUP et al, 2004;KUMAR, 2004) and only few of them were on tropical hardwood species (CALLISTER and COLLINS, 2008;SOTELO et al, 2007a;WEBER and SOTELO, 2008). In general, these studies reported similar heritability numbers compared to those found in clones of T. grandis; for example ED values from 0.14 to 0.17 in 19-year-old clones of Picea abies (HANNRUP et al, 2004), from 0.22 to 0.31 in 39 months old C. grandiflorum (SOTELO et al, 2007b) and 0.30 in mature douglas fir (CHERRY et al, 2008), 0.01 to 0.40 in 21 years old Pinus radiata (DUNGEY et al, 2006;GAPARE et al, 2010;KUMAR, 2004).…”
Section: Heritability Of Wood Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Inheritance of ED have been investigated during the last decade mainly concentrated in temperate species (CHERRY et al, 2008;DUNGEY et al, 2006;HANNRUP et al, 2004;KUMAR, 2004) and only few of them were on tropical hardwood species (CALLISTER and COLLINS, 2008;SOTELO et al, 2007a;WEBER and SOTELO, 2008). In general, these studies reported similar heritability numbers compared to those found in clones of T. grandis; for example ED values from 0.14 to 0.17 in 19-year-old clones of Picea abies (HANNRUP et al, 2004), from 0.22 to 0.31 in 39 months old C. grandiflorum (SOTELO et al, 2007b) and 0.30 in mature douglas fir (CHERRY et al, 2008), 0.01 to 0.40 in 21 years old Pinus radiata (DUNGEY et al, 2006;GAPARE et al, 2010;KUMAR, 2004).…”
Section: Heritability Of Wood Propertiesmentioning
confidence: 98%
“…There is topographical and soil characteristics differ among the studied tests. The experiment "Combate" presents a regular topography, with a soil type umbricepipedon and argillic horizon with high saturation of acidity, and on the other hand "San Cristobal" presents ultisol-type soil, with an argillic horizon and pH tend to be neutral.Numerous studies with clones of coniferous species report the effect of site on wood properties in older trees (GAPARE et al, 2010;HANNRUP et al, 2004;ZOBEL and VAN BUIJTENEN, 1989) but there has been less work on tropical hardwood species most notably with Guazuma crinita (WEBER and SOTELO, 2008), Dalbergia sissoo (PANDE and SINGH, 2005), Calycophyllum grandiflorum (SOTELO et al, 2007a), Bombacopsis quinata (HODGE et al, 2002) and Alnus acuminata (HERNÁNDEZ and RESTREPO, 1995), which are consistent with the effect of sites found in this work. Specifically in T. grandis in mature trees (14 years old), INDIRA and BHAT (1998) showed that site has a great influence on wood density.…”
mentioning
confidence: 99%
“…wood basic density (Apiolaza 2012;Gapare et al 2010Gapare et al , 2012aJohnson and Gartner 2006;Muneri and Raymond 2000), acoustic velocity or modulus of elasticity (Dungey et al 2012;Gapare et al 2012a;Jayawickrama et al 2011;Johnson and Gartner 2006), wood chemical properties (Sykes et al 2006), wood specific gravity (Jett et al 1991) and resin canal traits (Westbrook et al 2014). Osorio et al (2001) reported minimal G×E for wood density in Eucalyptus grandis in Colombia.…”
Section: Evidence Of G×e In Forest Treesmentioning
confidence: 99%
“…Studies in radiata pine have shown that there is little evidence of a genotype x environment interaction for wood density (Burdon and Low 1992;Gapare et al 2009;Wu et al 2008). This indicates that rank changes are unlikely between families with different levels of genetic improvement across different sites.…”
Section: Discussionmentioning
confidence: 99%